Olukumi: a dialect of Yoruba in diaspora (2016)
Much research attention has been devoted to Yoruba dialectology. Even some varieties of Yoruba spoken outside Nigeria have been included in the classifications of Yoruba dialects. However, 'Olukurni'. spoken in Aniocha North Local Government Area of Delta State, Nigeria, has been left out. This paper aims at investigating whether this speech form is actually a dialect of Yoruba language through the use of proven linguistic methods via lexicostatistics, mutual intelligibility and ethno-historical perception. The revised Swadesh list of 200 lexical items was used to obtain data from four native speakers of Olukumi. Two of these informants are traditional rulers who could be regarded as custodians of the history of the people. Mutual intelligibility reveals that this speech variety is intelligible to an average speaker of Yoruba. Lexicostatistic calculations gave us 68.5% when Olukumi is compared with the Standard Yoruba. However, when compared with llaje, the figure is higher. Oral accounts from our informants assert that the people migrated from the Ondo-Owo axis; had a stop-over in Benin and then migrated to their present location. From the foregoing, it can be concluded that the Olukumi people are Yoruba, however, their speech has been adulterated with borrowings from Igbo and Edo languages